C.1 - Gurdip Singh (New Delhi, 1985)
Third United Nations Conference on the Law of the Sea remained a political battlefield of the States for nearly a decade The States struggled to reshape the law of the sea and institutionalize the concept of "common heritage of mankind" by concluding a comprehensive Convention on the Law of the Sea. The Conference ended with the conclusion of a United Nations Convention on the Law of the Sea which poses a big challenge to maritime hegemonism and gears up the machinery o new International economic order. The Convention is a "package deal" and represents delicately balanced equilibrium of conflicting national interests. The issue of the nature and scope of dispute settlement machinery of the Convention plagued the initial stages of the Conference but was later resolved. This study proceeds on the premise that viable (and not supranational) dispute settlement machinery is essential for the stability and permanence of the Convention. It makes an endeavour to delineate the limits of compulsory international adjudicatory mechanisms of the dispute settlement machinery of the Convention. An analysis and evaluation of the general perspectives of compulsory international adjudication and its experiences at international and regional levels has been undertaken so as to tailor the compulsory international adjudicatory mechanisms of the Convention to fit into the prevailing political reality In addition to developing viable compulsory dispute settlement mechanisms of the Convention, the study emphasizes the need for enforcing the decisions of the maritime tribunals by suitable techniques which have been brought out in this work.
Keywords: International law